An International prevalence measurement of care problems: study protocol. (14th August 2013) - van, Noémi C.; Schols, Jos M.G.A.; Meesterberends, Esther; Lohrmann, Christa; Meijers, Judith M.M.; Halfens, Ruud J.G.
Abstract Aim The aim of this article was to describe the design of an international audit of the prevalence of care problems in different healthcare sectors using identical methodologies. Background Audits, defined as a monitor of quality of health care, are increasingly applied in many countries as a strategy to improve professional practice and quality and safety of care. A prerequisite to enable a reliable comparison of quality of care audits is the use of identical instruments and methodology. Design Annual cross‐sectional multi‐centre point prevalence survey. Method This international prevalence measurement of care problems in hospitals, care homes and home care is performed in the Netherlands, Austria, Switzerland and New Zealand. This study is based on a prevalence measurement of care problems originally performed in the Netherlands. For each care problem (pressure ulcer, incontinence, malnutrition, falls and restraints) at patient level, next to patient characteristics, data are gathered about the prevalence, prevention and treatment of each care problem. In addition, at ward/department and institution level, specific quality indicators are measured related to the care problems. After the measurement, institutions enter their data into a web‐based data‐entry program. Institutions receive an overview of their own results and results at national level to enable a process of benchmarking. Discussion A uniform way of measuring the prevalence of care problems internationally is a significant step forward in gaining insight into the quality of basic care in different healthcare settings in different countries and may lead to more awareness and improvement programmes.